Multi-omics analysis of two rat models reveals potential role of vesicle transport and autophagy in right ventricular remodeling - Yuhan Qin; Jing Zhang; Aiwei Wang; Wei Sun; Xiaohan Qin; Feng Qi; Yufei Wang; Le Du; Xiaoyan Liu; Haidan Sun; Zhengguang Guo; Xiaoxiao Guo (Scientific Reports)
Abstract Right ventricular failure as a severe consequence of pulmonary arterial hypertension (PAH) is an independent risk factor for poor prognosis, although the pathogenesis of right ventricular remodeling (RVR) remains unclear. Exploring the shared molecular pathways and key molecules in the right ventricle in monocrotaline (MCT) and pulmonary artery banding (PAB) rat models may reveal critical RVR mechanisms. Untargeted proteome and metabolome analysis were performed on the right ventricular myocardium of two RVR models (MCT-induced PAH rats and PAB-operated rats) to identify the altered proteins and metabolites, followed by validation using parallel reaction monitoring analysis and quantitative real-time polymerase chain reaction (qPCR). The multi-omics profiles of MCT and PAB rat models were compared to explore the key dysregulated molecules and pathways in RVR. Our proteomics study identified 25 shared RVR-altered differentially expressed proteins. Multiple common biological pathways were identified between PAB and MCT rat models, encompassing myocardial remodeling and energy metabolism alternation, etc. Various molecules and pathways related to vesicle transport and autophagy were identified, including nidogen-1, the soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs) signaling pathway, and the microautophagy pathway (all previously unreported in RVR). Glycerophospholipid metabolism was the sole statistically significant common metabolic pathway enriched by metabolomics. Underreported biological processes, including vesicle transport and autophagy, may contribute to the pathophysiology of PAH-induced RVR.